The Relationship Between Knowledge Level and Self-Efficacy on Self-Care Management in Chronic Kidney Failure Patients Undergoing Hemodialysis at Jakarta Cempaka Putih Islamic Hospital - Rahmi Ayu Safitri; ‎ Sofwan; Bahreni Yusuf; Hendik Wicaksono (JOURNAL EDUCATIONAL OF NURSING(JEN), 2026)
Background: Chronic Kidney Disease (CKD) patients undergoing hemodialysis require effective self-care management to support the success of their therapy. Knowledge and self-efficacy are important factors in managing self-care.  Objective: To determine the relationship between knowledge and self-efficacy levels with self-care management among CKD patients undergoing hemodialysis at the Jakarta Cempaka Putih Islamic Hospital. Methods: This study used a quantitative correlational design with a cross-sectional approach. The sample consisted of 75 CKD patients undergoing hemodialysis selected using simple random sampling. Data were collected using questionnaires on knowledge level, self-efficacy, and self-care management, and then analyzed using Chi-square tests and logistic regression. Results: Bivariate analysis showed a significant relationship between knowledge level and self-care management with a p value <0,001, as well as between self-efficacy and self-care management with a p value <0,001. Multivariate analysis showed that knowledge (OR = 6.633; p value < 0.001) and self-efficacy (OR = 10.633; p value < 0.001) had a significant effect on self-care management, with self-efficacy being the dominant factor. Conclusion: There is a significant relationship between the level of knowledge and self-efficacy with self-care management in CKD patients undergoing hemodialysis. Health education and emotional support are strongly needed to improve self-efficacy and knowledge so that patients' self-care management abilities can be enhanced.